Evaluating Cognitive Aspects of ADHD Students Using Brain-Computer Interface and a Digital Game: A Study in Brazil - Costa, Nayara Magda Gomes Barbosa da; Marçal, Edgar; Azevedo, Rafael Braz; Santos, Brenda Letícia Sousa dos; Carvalho, Meline Mesquita de (International journal of emerging technologies in learning, 2025)
In an academic setting, attention deficit hyperactivity disorder (ADHD) is a significant risk factor for suboptimal academic performance. A novel approach to the detection and treatment of children with ADHD is the brain-computer interface (BCI). The objective of this study was to develop and evaluate a computerized cognitive test (CCT) using a digital game and a BCI to identify and analyze differences in cognitive performance between students with and without ADHD. A qualitative-quantitative experimental study was conducted with 20 students’ aged 8 to 14, divided into two groups: 1) 10 with ADHD and 2) 10 without ADHD. At the outset of the study, a semi-structured interview was conducted to obtain an initial understanding of the participants’ backgrounds and medical histories. Subsequently, neuropsychological tests were administered for the purpose of assessing cognitive levels. Following this, the BCI was used in conjunction with the digital game. The neuropsychological instruments yielded statistically significant results between the two samples. The results of the CCT indicated that students without ADHD exhibited superior performance in eight of the nine analyzed criteria. The utilization of a digital game integrated with a BCI can assist in the identification of cognitive aspects that distinguish children with and without ADHD. Moreover, individuals diagnosed with ADHD demonstrated enhanced performance across all phases of the game.